On the development of a new flexible drill for orthopedic surgery and the forces experienced on drilling bovine bone. (May 2018) - Ahmad Fuad, Ahmad Nazmi Bin; Deep, Kamal; Yao, Wei; Rowe, Philip
This article presents the construction of a flexible drill which is designed to cut a curved canal in the bone or remove bone materials, to improve the outcome of orthopedic surgery and to facilitate minimally invasive. This article reports the design of the flexible drill and uses it in an experimental rig to evaluate the drilling force generated when cutting bovine bone. The experiments facilitate the measurement of action forces between the mill bits when moving the tip toward or across a bone sample in various configurations caused by bending the flexible drill sheath to enable cutting of a curved path of variable radius in the bone. The reaction force represents the force trying to deflect the mill bit tip away from the bone sample surface and must be resisted in order to continue cutting without deflection or buckling of the tip during the drilling of curved pathways. The experiment shows the flexible drill can cut bones in both configurations and experienced a maximal force of 3.4N in the vertical configuration and 0.54N in lateral configuration. The experimental results show that the flexible drill designed is able to produce sufficient force at variable bending angles to perform the required tasks for bone cutting.